2009
DOI: 10.1590/s1519-69842009000500003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human trampling on a rocky shore fauna on the Sao Paulo coast, southeastern Brazil

Abstract: Increased tourist activity in coastal regions demands management strategies to reduce impacts on rocky shores. The highly populated coastal areas in southeastern Brazil are an example of degradation caused by development of industry and tourism. Among different shore impacts, trampling has been intensively studied, and may represent a significant source of stress for intertidal fauna. A randomised blocks design was applied to experimentally study the effects of two different trampling intensities on richness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
(26 reference statements)
0
20
0
2
Order By: Relevance
“…Trampling can negatively affect both the density and biomass of assemblages of organisms in sandy beaches (Veloso et al, 2006;Coombes et al, 2008;Lucrezi et al, 2009aLucrezi et al, , 2009b, salt marshes (Martone and Wasson, 2008), mudflats (Rossi et al, 2007) and rocky shores (Smith and Murray, 2005;Ferreira and Rosso, 2009). Thus it is important to quantify the impacts of trampling for better management and conservation of coastal areas that are subjected to frequent human activity (see reviews by Davenport and Davenport, 2006;Defeo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Trampling can negatively affect both the density and biomass of assemblages of organisms in sandy beaches (Veloso et al, 2006;Coombes et al, 2008;Lucrezi et al, 2009aLucrezi et al, , 2009b, salt marshes (Martone and Wasson, 2008), mudflats (Rossi et al, 2007) and rocky shores (Smith and Murray, 2005;Ferreira and Rosso, 2009). Thus it is important to quantify the impacts of trampling for better management and conservation of coastal areas that are subjected to frequent human activity (see reviews by Davenport and Davenport, 2006;Defeo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…re cruits or seedlings) may be more susceptible to trampling damage, especially in monospecific stands and areas dominated by a few species. Tests of this third mechanism are lacking.Barnacles represent one of the best studied taxa with respect to trampling (Zedler 1978, Beauchamp & Gowing 1982, Povey & Keough 1991, Brosnan 1994, Jenkins et al 2002, Ferreira & Rosso 2009). However, previous barnacle trampling studies ignored other important disturbances (e.g.…”
mentioning
confidence: 99%
“…Studying trampling in isolation from other disturbances may have created some of the uncertainty associated with the influence of trampling on barnacles. For example, footsteps can lower barnacle survivorship (Povey & Keough 1991) and trampling additions can reduce barnacle cover (Brosnan 1994, Ferreira & Rosso 2009. However, several studies found no effect of trampling on barnacle cover (Jenkins et al 2002) or density (Beauchamp & Gowing 1982, Goldstein 1992.…”
mentioning
confidence: 99%
“…Visitor density estimates were made by obtaining: visitation rates based on timed visitor counts, the area of the habitat exposed at the desired tide level, and determining the annual hours of rocky intertidal exposure. In contrast, it may be more difficult to manage the impacts of foot traffic using information from studies incorporating foot step density as the experimental metric (Povey and Keough 1991, Keough and Quinn 1998, Ferreira and Rosso 2009, Huff 2011, for which a scale of footsteps per person would have to be calculated and, which to date, has not been calculated. For this reason, the visitor density metric and calculation methods presented here may be more valuable to resource managers addressing impacts to rocky intertidal communities than metrics used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…While this comprehensive approach was to provide greater support for park management decisions on resource protection, it was also designed and executed to overcome some of the shortcomings of previous studies of human disturbance in natural areas that have been the subject of considerable previous research (e.g., Chan 1970, Underwood and Kennelly 1990, Keough and Quinn 1998, Schiel and Taylor 1999, Murray et al 1999, Ambrose and Smith 2004, Van De Werfhorst and Pearse 2007 (Chan 1970, Ferreira and Rosso 2009. Changes in species abundance levels and distribution can also result from illegal collecting and from trampling.…”
Section: Introductionmentioning
confidence: 99%